Multidetector computed tomography angiography study of the renal arterial vasculature anatomy and its variations in a Bulgarian adult population. - Mihaylova, Evgeniya; Groudeva, Violeta; Nedevska, Maria (Surgical & Radiologic Anatomy, 2023)
Purpose: Renal arterial anatomy has a great clinical importance during surgical and endovascular procedures. However, comprehensive data on renal arterial variations in the Bulgarian population has not yet been provided. The aim of this study was to conduct a detailed research about the normal anatomy and variations of the renal arteries in the Bulgarian population. Methods: Five hundred sixty-one patients underwent contrast-enhanced multidetector computed tomography scans for the period 2016–2021. The images were retrospectively reviewed. Number, branching pattern, origin level and course of the renal arteries were noted. Data were categorized on the basis of laterality, gender and symmetry. Results: Only 46.3% of the patients exhibited normal renal arterial anatomy. Variations were observed in 301 patients (53.7%). The most common variant was the presence of accessory renal arteries (ARA), discovered in 41.2% of the subjects. There was no significant difference based on gender and laterality (p > 0.05). Hilar ARA (72.6%) were significantly more common than polar ARA (p < 0.001). The most common origin location of the main renal arteries and ARA was the aorta, followed by the common iliac arteries. Early division was observed in 21.7% of the patients, significantly more common on the right. Precaval course was found in 0.5% of the right main renal arteries and in 30% of ARA and the difference was significant (p < 0.001). Conclusion: These results show novel insight into the prevalence of renal arterial variations in the Bulgarian population. Anatomic renal vasculature variants are common therefore awareness is crucial for the success of surgical and interventional procedures.